2005
DOI: 10.4269/ajtmh.2005.72.675
|View full text |Cite
|
Sign up to set email alerts
|

Anti–plasmodium Vivax Duffy Binding Protein Antibodies Measure Exposure to Malaria in the Brazilian Amazon

Abstract: Plasmodium vivax Duffy binding protein (DBP) is functionally important in the erythrocyte invasion process and provides a logical target for vaccine-mediated immunity. In the current study, we demonstrated that DBP is naturally immunogenic in different populations of the Brazilian Amazon, and the proportions of DBP IgG positive subjects increased with exposure to malaria, reaching a peak in those subjects with long-term exposure (> 15 years) in the Amazon area. This profile of antibody response was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 36 publications
4
47
1
7
Order By: Relevance
“…Our analysis showed that the frequency of responders to PvAMA-1 and PvDBP-RII was higher in the multiple-infected. This data suggests that multiple infections provide a boost to the production of specific antibodies confirming recent observations obtained in other studies in distinct endemic areas of Brazilian Amazon (Ceravolo et al 2005, Tran et al 2005). In the case of PvMSP1 19 , specific IgG responses developed faster after a single exposition to malaria infection, also confirming previous observations of distinct groups that PvMSP1 19 is highly immunogenic during natural human infections (Park et al 2001, Lim et al 2002, Rodrigues et al 2003, Morais et al 2005, Wickramarachchi et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis showed that the frequency of responders to PvAMA-1 and PvDBP-RII was higher in the multiple-infected. This data suggests that multiple infections provide a boost to the production of specific antibodies confirming recent observations obtained in other studies in distinct endemic areas of Brazilian Amazon (Ceravolo et al 2005, Tran et al 2005). In the case of PvMSP1 19 , specific IgG responses developed faster after a single exposition to malaria infection, also confirming previous observations of distinct groups that PvMSP1 19 is highly immunogenic during natural human infections (Park et al 2001, Lim et al 2002, Rodrigues et al 2003, Morais et al 2005, Wickramarachchi et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…28,33 However, the serologic responses of residents in vivax malaria-endemic regions did show a positive correlation with exposure and host age, as shown in the previous studies. 23,28,30,44 This result suggests a possible boosting of the PvDBP-II antibody response because of accumulated age-related exposure.…”
Section: Discussionmentioning
confidence: 63%
“…28,32 As shown by several studies, selection of an antigen for vaccination requires a detailed understanding of natural immune responses elicited by the protein from different malariaendemic regions with various epidemiology, and the result of similar studies from one malaria-endemic region cannot be extrapolated to other areas of malaria-endemic regions in the world. 33 Therefore, the current investigation was designed, Abstract. Plasmodium vivax remains an important cause of morbidity outside Africa, and no effective vaccine is available against this parasite.…”
Section: Introductionmentioning
confidence: 99%
“…Although two previous Brazilian studies did not show this tendency for the N-terminal of the P. vivax MSP-1, 9, 28 our data are in agreement with another study in which the proportion of responders to PvMSP-1 variants increased during subsequent infections. 38 Moreover, in studies that evaluated the C-terminal of the MSP-1 31 and other parasite proteins, such as DBP-II 39,40 and AMA-1 31,41 a positive correlation was also observed between the increase in the antibody response and the number of past malaria episodes. These data taken together suggest that multiple infections can provide a boost for the production of the specific antibodies.…”
Section: Discussionmentioning
confidence: 93%